Tahapan Legislasi Perda Wajib Belajar 12 Tahun di Kota Bukittinggi: Sebuah Studi Proses dan Implementasi Kebijakan - Fadilul Rahman (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Secondary education plays an important role in shaping the character and competence of the younger generation. However, challenges in access and quality gaps are still obstacles in the regions, including Bukittinggi City. This study aims to explain the process of drafting the Regional Regulation (Perda) on 12-Year Compulsory Education in Bukittinggi City as an effort to expand access to secondary education. The approach used is a case study with a public policy perspective. The results of the study show that the Perda legislation process goes through the stages of identifying issues of low education participation, setting the agenda in the Prolegda, raising political legitimacy, formulating academic papers and Draft Perda, discussing and ratifying by the DPRD, to the implementation stage through socialization and supporting policies. The conclusion shows that this Perda legislation is a multi-actor collaboration and reflects the region's commitment to educational equality, although it still faces implementation challenges that require evaluation and strengthening of further policies.